Faktor-Faktor Yang Mempengaruhi Current Ratio, Debt Equity Ratio, Debt Asset Ratio, Dan Perputaran Modal Kerja Terhadap Return On Asset - Vina Ramaadhianti; Wafiyyah Septiwidya; Juwainah Juwainah; Anditha Wanda Salsabila; Avriliani Dwi Septianay; Tri Yulaeli (Student Scientific Creativity Journal, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research serves to strengthen the theory and phenomenon of the relationship or influence between returns on assets. This article reviews the factors that influence the current ratio, debt equity ratio, and debt asset ratio in an introductory financial management literature study. This study aims to analyze the factors that influence the disclosure of Return on Assets, namely: current ratio, debt equity ratio, debt-asset ratio, and working capital turnover. Samples were selected using purposive sampling method and samples that met the criteria. This study uses the classical assumption test, model feasibility test, multiple regression analysis and statistical t test. These results indicate that the variable current ratio and debt equity ratio have an effect on return on assets, while the debt-asset ratio and working capital turnover variable have no effect on return on assets.